Distal radius morphometry in the Malaysian population - Chan, C.Y.W.; Vivek, A.S.; Leong, W.H.; Rukmanikanthan, S. (2008)
The goal of treatment in distal radius fracture is to restore the anatomy of the distal radius, however the criteria currently used to evaluate the quality of reduction are based on Western based published figures. This goal of this study was to investigate whether there are variations in the morphology of the distal radius among the multiracial population of Malaysia. Consecutive normal wrist radiographs of patients who presented to the accident and emergency unit in three major hospitals in Malaysia were measured. . The palmar tilt of the distal radius averaged 12.6o Â± 3.55o, and the radial inclination averaged 25.1o Â± 3.42o. The ulnar variance averaged â 0.1 Â± 1.31mm, 38.4 of the patients had neutral ulnar variance, 28.8 have negative ulnar variance and 32.9 have positive ulnar variance. Our results indicate that distal radius morphometric parameters in the Malaysian population are comparable to Western figures.